2009
DOI: 10.1073/pnas.0901452106
|View full text |Cite
|
Sign up to set email alerts
|

Bam and Bgcn antagonize Nanos -dependent germ-line stem cell maintenance

Abstract: The balance between germ-line stem cell (GSC) self-renewal and differentiation in Drosophila ovaries is mediated by the antagonistic relationship between the Nanos (Nos)-Pumilio translational repressor complex, which promotes GSC self-renewal, and expression of Bam, a key differentiation factor. Here, we find that Bam and Nos proteins are expressed in reciprocal patterns in young germ cells. Repression of Nos in Bam-expressing cells depends on sequences in the nos 3-UTR, suggesting that Nos is regulated by tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
205
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(219 citation statements)
references
References 48 publications
11
205
1
2
Order By: Relevance
“…GSCs express the translational repressor Nanos, a factor essential for GSC maintenance. On displacement away from the cap cell niche, GSC daughters express Bam, which represses the translation of nanos in differentiating cysts (30). Costaining control and Lsd1 mutant germaria for Nanos and Bam revealed that less than 1.5% of Lsd1 mutant germaria expressed detectable levels of Bam (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GSCs express the translational repressor Nanos, a factor essential for GSC maintenance. On displacement away from the cap cell niche, GSC daughters express Bam, which represses the translation of nanos in differentiating cysts (30). Costaining control and Lsd1 mutant germaria for Nanos and Bam revealed that less than 1.5% of Lsd1 mutant germaria expressed detectable levels of Bam (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1C). To express sgRNA in vivo, we selected three different regulatory sequences: U6a (CR31379) and U6b (CR32867) (26,27), both of which direct transcription of Drosophila U6 snRNAs, and nosmini, which contains the nos promoter and a minimal 5′ UTR (28,29). We used the 404-bp upstream and 93-bp downstream regulatory sequences of U6a to construct U6a-sgRNA-short and U6a-sgRNA-long.…”
Section: Methodsmentioning
confidence: 99%
“…Nanos promotes GSC fate, whereas Bam promotes differentiation. These antagonistic activities were shown to depend on the repression of nanos mRNA translation by the Bam/Bgcn complex, possibly via nanos 3′UTR (9). In this model, Bam would thus promote differentiation by inhibiting stem cell-promoting factors, which is different from inhibiting self-renewal by stabilizing differentiation factors, such as CycA.…”
mentioning
confidence: 99%
“…Here, it is important to have in mind in which cell types these proteins are endogenously expressed to distinguish gain-vs. loss-of-function experiments. Bam and Nanos proteins are expressed in nonoverlapping reciprocal domains, with Nanos expressed in GSCs and 16-cell cysts, whereas Bam protein is found exclusively during the four mitotic divisions (9). Bgcn and Otu are expressed throughout the germarium.…”
mentioning
confidence: 99%